Interactions Between Beet necrotic yellow vein virus and Beet soilborne mosaic virus in Sugar Beet - Wisler, G C (Plant disease, 2003)
Soils naturally infested with cultures of aviruliferous Polymyxa betae and viruliferous P. betae carrying two sugar beet benyviruses, Beet necrotic yellow vein virus (BNYVV) and Beet soilborne mosaic virus (BSBMV), alone and in combination, were compared with noninfested soil for their effects on seedling emergence, plant fresh weight, and virus content as measured by enzyme-linked immunosorbent assay (ELISA). Studies examined sugar beet with and without resistance to the disease rhizomania, caused by BNYVV. The Rz gene, conferring resistance to BNYVV, did not confer resistance to BSBMV. BSBMV ELISA values were significantly higher in single infections than in mixed infections with BNYVV, in both the rhizomania-resistant and -susceptible cultivars. In contrast, ELISA values of BNYVV were high (8 to 14 times the healthy mean) in single and mixed infections in the rhizomania-susceptible cultivar, but were low (approximately three times the healthy mean) in the rhizomania-resistant cultivar. Results indicate BNYVV may suppress BSBMV in mixed infections, even in rhizomania-resistant cultivars in which ELISA values for BNYVV are extremely low. Soils infested with P. betae, and with one or both viruses, showed significantly reduced fresh weight of seedlings, and aviruliferous P. betae significantly decreased sugar beet growth in assays